Advanced fabrication for electrospun three-dimensional nanofiber aerogels and scaffolds - Yujie Chen (Bioactive Materials, 2020)
Electrospinning is a versatile strategy for creating nanofiber materials with various structures, which has broad application for a myriad of areas ranging from tissue engineering, energy harvesting, filtration and has become one of the most important academic and technical activities in the field of material science in recent years. In addition to playing a significant role in the construction of two-dimensional (2D) nanomaterials, electrospinning holds great promise as a robust method for producing three-dimensional (3D) aerogels and scaffolds. This article reviews and summarizes the recent advanced methods for fabricating electrospun three-dimensional nanofiber aerogels and scaffolds, including gas foaming, direct electrospinning of 3D nanofibrous scaffold, short nanofibers assembling into 3D aerogels/scaffolds, 3D printing, electrospray, origami and cell sheet engineering, centrifugal electrospinning, and other methods. Besides, intriguing formation process, crosslinking pathway, properties, and applications of 3D aerogels and scaffolds are also introduced. Taken together, these aerogels and scaffolds with various excellent features present tremendous potential in various fields.